Kochanek Sybilli Thompson Marii Pawlikowskiej-Jasnorzewskiej – Utopia czy dystopia? - Aleksandra E. Banot (Studia Slavica)
Maria Pawlikowska-Jasnorzewska’s futurological fantasy from 1926 entitled Kochanek Sybilli Thompson (The Lover of Sybilla Thompson) seems to be a realistic social utopia. On the one hand, it reflects the spirit of the moral revolution of the interwar period and refers to the beginnings of aesthetic medicine and cosmetic treatments aimed at rejuvenation. On the other hand, it heralds – how aptly – the era of hippie free love, polyamorous relationships of the 1970s, the time of the next sexual revolution, but also the time of much more advanced plastic surgeries and cosmetic technologies. However, a careful reading of the drama allows us to see the critical (and also satirical) dimension of the story about a seventy eight-year-old woman who decided to rejuvenate herself in order to experience physical love once again. Joyful utopia becomes sad dystopia. In my article I look at this dualism: utopian – dystopian, realistic – fantastic, joyful – sad, young – old, modern – conservative, and the game of tension between oppositional concepts.